Efficacy and safety of tacrolimus-based treatment for non-rapidly progressive IgA nephropathy - Zhao, Lijuan; Yang, Yanyan; Xu, Hao; Leng, Wei; Xu, Guoshuang (Frontiers in Pharmacology, 2023)
In this study, we aimed to evaluate the efficacy and safety of tacrolimus-based treatment for immunoglobulin A nephropathy (IgAN). We retrospectively reviewed 127 adult patients with primary IgAN with 24h urine total protein quantity (24hUTP) ≥ 1 g and serum creatinine ≤ 3 mg/dL. All patients were divided into tacrolimus (TAC) and control (non-TAC) groups according to the treatment strategy. Proteinuria remission, remission rate, and adverse events were compared between the two groups. Among the 127 patients, 61 received TAC-based treatment and 66 received non-TAC treatment. TAC group exhibited a more rapid decline in proteinuria than the non-TAC group at 3, 9 and 12 months (P = 0.049, 0.001 and 0.018, respectively). Remission rates at 1, 3, 6, 9, and 12 months were 41.0, 68.9, 80.3, 90.2, and 88.5%, respectively, in the TAC group. These rates were higher than those in the control group at 3, 9, and 12 months (P = 0.030, 0.008, and 0.026, respectively). Complete remission rates at 1, 3, 6, 9, and 12 months were 6.56, 19.7, 37.7, 54.1, and 62.3%, respectively, in the TAC group. These rates were higher than those in the control group at 9 and 12 months (P = 0.013 and 0.008, respectively). The estimated mean time to complete remission was significantly shorter in the TAC group than in the control group (P = 0.028). TAC did not increase the incidence of adverse events. In conclusion, TAC accelerated proteinuria remission in patients with non-rapidly progressive IgAN with no increased risk of adverse events. Further prospective randomized controlled trials are necessary to validate our findings,